Transformative Adult Education: Transformative learning experiences, in the self-evaluation of participants in the BA for Personal and Professional Development (ALBA), All Hallows College, Dublin, on completion of their first year of studies. - Ó Mathúna, Ciarán (All Hallows College (DCU), 2019)
Educational theory tells us that adults who return to formal education often experience personal transformations as a result of their engagement with the education process. This can have a profound effect on a person’s self-concept, their relationships, work life choices and active participation in society. As a practicing adult educationalist I have many examples of witnessing adults experiencing personal change as a result of participation in a programme of study. Within an Irish context, the difficulty has been capturing these personal transformations in an empirical, validated, and trustworthy manner rather than as anecdotal stories. This thesis is a structured systematic research project to capture such transformations. Through narrative interviews, the transitional and transformative experiences of thirty-two participants on the BA for Personal and Professional Development (ALBA) course were gathered, analysed and referenced to the theory of Transformative Learning and the work of Jack Mezirow. The analysis is able to confirm the existence of transformative learning and personal transformations. The results of this research show an increase in personal confidence along with broader personal, social and academic horizons. As a result of this research implications arise for education providers; most notably; students need assistance in the transition to academia; the provision of a ‘Foundations’ programme; and ongoing structured supports throughout their study.
Keywords: Adult Education